Relasi Budaya Arab-Melayu dalam Sejarah di Indonesia - Madjid, M. Dien (Buletin Al-Turas, 2013)
Abstract This research reveal about culture of Arab-Malay could not escape the series of Islamization that is not separated from the contribution of the Arab nation. From man of the desert this is Islam exuberantly and check in Malay. His natural aridity, does not affect the subtlety of the attitude and friendliness of speak so unable to convince the population of the Islands for religious Unity. Of those entities in order to at maturity, and can synergize with the global community. The synergy of trade-Da'wah is no longer the offensive problems of Commerce, here in after have led to the phenomenon of history to mixture of both cultures. People Arabic or Malay has a cultural attachment that cannot be released. This makes the second Southeast Asian ethnic group as a vehicle of Islamic civilization in the other country of origin faced. In the regional area, nesting and Islamic showed to its light able to be felt until the present. Culture that woke up, became the unifying node that displays an openness and smoothness is maintained in a long time. This paper will peel back the issue of how Arab-Malay articulation happen and dialectical. ---Â Abstract Penelitian ini mengungkap tentang kebuadaayan Arab-Melayu tidak bisa lepas dari rangkaianÂ  Islamisasi yang tidak lepas dari kontribusi bangsa Arab. Dari manusia padang pasir inilah Islam merimbun dan menyemak di lingkungan Melayu. Kegersangan alam tempat tinggalnya, tidak mempengaruhi kehalusan sikap dan keramahan bertutur sehingga mampu meyakinkan penduduk kepulauan untuk beragama Tauhid. Dari mereka entitas kemelayuan sampai pada maturitas, hingga dapat bersinergi dengan komunitas global. Sinergi dagang-dakwah bukan lagi menyinggung masalah perniagaan, selanjutnya telah membawa pada fenomena menyejarah yakni percampuran budaya keduanya. Orang Arab maupun Melayu memiliki keterikatan kultural yang tidak bisa dilepaskan. Kedua etnis ini menjadikan Asia Tenggara sebagai wahana tampilnya peradaban Islam yang berwajah lain dari negeri asalnya. Di kawasan regional tersebut, Islam bersarang dan menerang hingga sinarnya mampu dirasakan hingga masa kini. Budaya yang terbangun, menjadi simpul pemersatu yang menampilkan kehalusan dan keterbukaan yang terjaga di waktu yang lama. Makalah ini akan mengupas masalah bagaimana akluturasi Arab-Melayu terjadi dan berdialektika.